Whiteness as an Immunity Badge - Nsiangani, Kibavuidi (USK Journal of Political Science and Epistemology, 2023)
This paper argues that “white man,” “whiteness,” and related expressions in anti-colonial and revolutionary discourse function primarily as system-role shorthand rather than biological hatred of individuals. In contemporary debate, however, participants who explicitly defend colonial or neocolonial arrangements use a common conversion move that recodes institutional critique into phenotype-based accusation. I formalize this recurring move as the deflection slide: system critique (Frame S) is shifted to interpersonal race morality (Frame P), typically followed by inversion tokens such as “anti-white racism,” “I didn’t do anything to you,” “colorblindness,” or the claim that critics demand apology for being white or are “essentializing” whiteness. Using a compact evidence pack drawn from a larger corpus of public conversations across Facebook, Twitter, and forums (n=782) and supported by interview excerpts (n=75), this paper shows the slide’s consistency across platforms and settings, including a captured-script variant reproduced by some participants who self-position as ‘pro-Western’ or ‘neutral’ within the exchange. The analysis clarifies how the deflection slide essentializes whiteness as innocent identity under attack while pinning culpability on those who name oppression, thereby preserving the legitimacy and continuity of colonial ideology in the present tense. The paper closes with a simple falsification test that any reader can run, to demonstrate that this observable contemporary mechanism is not a mere posteriori interpretation.
The Deflection Slide: Converting System Critique into “Anti-White Racism” to Restore Moral Immunity
Clarifications, Scope, and Sequencing of the Research Program This paper is the first in a two-paper sequence. Its purpose is construct clarification and mechanism demonstration, not prevalence estimation. It specifies how “whiteness” functions as an ideological-discursive name and how a predictable interaction pattern converts structural critique into an accusation of interpersonal racism. It then interprets the pattern clinically as mirroring three control styles that map to the Dark Tetrad family: narcissistic gaslighting, psychopathic banalisation, and sadistic humiliation, enacted either by direct system-defenders or by participants exhibiting captured-script reproduction (CAP) within the exchange. Prevalence quantification, trait frequency estimation, and cross-platform distribution belong to the next paper (“Troll Labs”), which will quantify these traits at scale in public discourse. On the use of “whiteness”: As obvious as it is, I do not believe in a monolithic “white” identity. What is termed ‘whiteness’ here is not my perception of a homogeneous group, but a colonial discursive code: a shorthand for system-role positioning. I do not treat it as a biological essence. In simpler terms, my unit of analysis is the move, not the identity. All coding is content-based and applies to discursive moves, not demographic identities or clinical diagnosis of individuals. (Dataset A–D)
Keywords: whiteness; colonialism; neocolonialism; deflection; reverse racism; discourse mechanism; moral immunity; epistemic capture; anti-colonial rhetoric.